Urine retention as presenting manifestation of tuberculous meningitis complicated by lacunar infarction and transverse myelitis: Case report and literature review - Ahmed Salih Abdulhadi (14777632) (2021)
Early diagnosis and management of tuberculous meningitis will prevent lethal and fatal neurological complications such as acute infarction and permanent disability. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.4489